Pengaruh Kualitas Pelayanan dan Kualitas Produk terhadap Kepuasan Pelanggan UNIQLO Living World Pekanbaru - Hidayat, Rahmadani; Ardianto, Bagus; Nusyirwan, Nusyirwan (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2024)
Abstract The aim of this research is to determine the effect of service and product quality on UNIQLO Living World Pekanbaru customer satisfaction. The respondents for this research were 100 people using random samples. The data analysis technique used to answer the hypothesis is multiple regression, classical assumption test, F hypothesis test, t hypothesis test, coefficient of determination using SPSS 25 and Microsoft Excel 2016. The research results show that service quality and product quality have a positive influence. influences student satisfaction both partially and simultaneously. From the results of the coefficient of determination test (R2), it is known that the two independent variables contribute 52.9% in influencing the dependent variable, namely customer satisfaction in choosing UNIQLO Living World Pekanbaru products.